Patient and Provider Risk in Managing ST-Elevation Myocardial Infarction During the COVID-19 Pandemic: A Decision Analysis. (November 2020) - Butala, Neel M.; Patel, Nilay K.; Chhatwal, Jagpreet; Vahdat, Vahab; Pomerantsev, Eugene V.; Albaghdadi, Mazen; Sakhuja, Rahul; Rosenzweig, Anthony; Elmariah, Sammy
Abstract : Background: The optimal treatment strategy for treating ST-segment–elevation myocardial infarction (STEMI) in context of the coronavirus disease 2019 (COVID-19) pandemic is unclear given the potential risk of occupational exposure during primary percutaneous coronary intervention (PPCI). We quantified the impact of different STEMI treatment strategies on patient outcomes and provider risk in context of the COVID-19 pandemic. Methods: Using a decision-analytic framework, we evaluated the effect of PPCI versus the pharmaco-invasive strategy for managing STEMI on 30-day patient mortality and individual provider infection risk based on presence of cardiogenic shock, suspected coronary territory, and presence of known or presumptive COVID-19 infection. Results: For patients with low suspicion for COVID-19, PPCI had mortality benefit over the pharmaco-invasive strategy, and the risk of cardiac catheterization laboratory provider infection remained very low (<0.25%) across all subgroups. For patients with presumptive COVID-19 with cardiogenic shock, PPCI offered substantial mortality benefit to patients relative to the pharmaco-invasive strategy (7.9% absolute decrease in 30-day mortality), but also greater risk of provider infection (2.3% absolute increase in risk of provider infection). For patients with presumptive COVID-19 with nonanterior STEMI without cardiogenic shock, PPCI offered a 0.4% absolute mortality benefit over the pharmaco-invasive strategy with a 0.2% greater absolute risk of provider infection, and the tradeoff between patient and provider risk with PPCI became more apparent in sensitivity analysis with more severe COVID-19 infections. Conclusions: Usual care with PPCI remains the appropriate treatment strategy in the majority of cases presenting with STEMI in the setting of the COVID-19 pandemic. However, utilization of a pharmaco-invasive strategy in selected patients with STEMI with presumptive COVID-19 and low likelihood of mortality from STEMI and use of preventive strategies such as preprocedural intubation in high risk patients when PPCI is the preferred strategy may be reasonable to reduce provider risk of COVID-19 infection. Abstract : Supplemental Digital Content is available in the text.